Integrative Systems Biology Analysis Elucidates Mastitis Disease Underlying Functional Modules in Dairy Cattle - Ghahramani, Nooshin; Shodja, Jalil; Rafat, Seyed Abbas; Panahi, Bahman; Hasanpur, Karim (Frontiers in Genetics, 2021)
Background: Mastitis is the most prevalent disease in dairy cattle and one of the most significant bovine pathologies affecting milk production, animal health, and reproduction. Additionally, mastitis is the most common, expensive, and contagious infection in the dairy industry. Materials and Methods: A meta-analysis of microarray and RNA-Seq data was conducted to identify candidate genes and functional modules associated with mastitis disease. The results were then applied to systems biology analysis via weighted gene co-expression network analysis (WGCNA), gene ontology (GO), enrichment analysis for the Kyoto Encyclopedia of Genes and Genomes (KEGG), and modeling using machine learning algorithms. Results: Microarray and RNA-Seq datasets were generated for 2089 and 2794 meta-genes, respectively. Between microarray and RNA-Seq datasets, a total of 360 meta-genes were found that were significantly enriched as "Peroxisome," "NOD-like receptor signaling pathway," "IL-17 signaling pathway," and "TNF signaling pathway" KEGG pathways. The turquoise module (n = 214 genes) and the brown module (n = 57 genes) were identified as critical functional modules associated with mastitis through WGCNA analysis. PRDX5, RAB5C, ACTN4, SLC25A16, MAPK6, CD53, NCKAP1L, ARHGEF2, COL9A1, and PTPRC genes were detected as hub genes in identified functional modules. Finally, using attribute weighting and machine learning methods, hub genes that are sufficiently informative in Escherichia coli (E. coli) mastitis were used to optimize predictive models. The constructed model proposed the optimal approach for the meta-genes and validated several high-ranked genes as biomarkers for E. coli mastitis using the decision tree (DT) method. Conclusion: In conclusion, the candidate genes and pathways proposed in this study may shed new light on the underlying molecular mechanisms of mastitis disease and suggest new approaches for diagnosing and treating E. coli mastitis in dairy cattle.